A Comparative Study Of The Implementation Of A Closed Proportional System In The Perspective Of A Country With A Presidential System - Kolopita, Kurnia Ningsih Kolopita; Rahim, Erman I.; Ahmad, Ahmad (Estudiante Law Journal, 2024)
This research aims to analyze the comparison of the implementation of a closed proportional system between Indonesia and countries that adhere to the presidential system through normative research methods with a fact approach and conceptual approach. By using the theory of elections, the theory of political parties and the theory of justice. Legal materials are collected through literature study and then analyzed and compared based on the object of research. The results of this study found several differences in the implementation of proportionality systems in several countries such as Mexico, Brazil and Argentina, each of which applies a proportional system based on the needs and conditions of the country.